Interaction effect of iron and defatted soybean (Glycin max L.) supplementation to wheat (Triticum aestivum G.) flour on hemoglobin regeneration efficiency of growing male rats - Khalid Hammady Hameed Sharaf (College of Education for Pure Sciences, 2008)
ABSTRACT Wheat flour (WF) of 85% meal extraction was blended with or without defatted soybean flour (DSF) meal and enriched with 50 or 100mg iron/kg diet. Experimental diets (WF control, WF+50mg iron, WF+100mg iron, WF+50g DSF, WF+50g DSF+50mg iron and WF+50g DSF+100mg iron) were prepared and used for protein digestibility and hemoglobin regeneration efficiency studies. Sixty male weanling albino rats were used as a biological and experimental model for this study, rats were divided into two equal major groups. The first group (healthy rats) divided into six subgroups according to the hemoglobin (Hb) value fed experimental diets separately for 10 days period. The second group was iron depleted by removing 20-25 drops of blood from ocular vein by using capillary tube and considered to be anemic rats, divided and fed diets as a above. Analysis of variance showed that, the protein digestibility index of the healthy rats was higher than that index of the anemic rats. Apparent iron absorption was positively proportional to the dietary iron enrichment. DSF protein was improved the dietary iron absorption of the rats. The dietary iron absorption of the anemic rats was higher than that absorption of the healthy rats. Hb value, Hb iron gain and HRE were increased with increase dietary iron level (18-121mg/kg diet) in both trails of rats. HRE% of the anemic rats was higher than that ratio of the healthy rats. WF+50gDSF+50gm iron diet was found to improve protein digestibility, dietary iron absorption and HRE in rats.